American Weed: A History of Cannabis Cultivation in the United States - Nick Johnson (EchoGéo)
The illegal cultivation of cannabis in the United States has a long history, the weight of which is currently propelling a number of US states to legalize and regulate the plant after more than eighty years of outright prohibition. While each region has its own distinct history with the crop, this article outlines the history of cannabis cultivation in three parts of the country – the Midwest, South, and West – in an attempt to map out the driving social, economic, geographic, and environmental forces of illegal (and in some cases, legal) cannabis cultivation in the United States. Understanding how the US became one of the premier cannabis-growing regions of the world in the late twentieth and twenty-first centuries will help scholars pinpoint major themes in the world history of cannabis, such as its adoption and distribution by marginalized peoples, its transnational appeal in a globalized capitalist system, and how the plant embeds itself within the urban and rural ecology of human civilization. With a clearer picture of these themes, cannabis scholarship can better inform future studies, discussions, and public policy related to the plant.